Group of teenage boys and girls dancing - Unknown:::Creator::::::::::::
Photograph shows a group of teenage boys and girls dancing. There is a group of girls sitting on a bench along a mirrored wall. Two women are standing on the right hand side in the background and are probably chaperones.